Interpretasi Kritis atas Sistem Sosial dan Sejarah Pendidikan Islam Modern Pasca Tragedi 11 September 2001 - Syahrul, Syahrul; Syalviana, Evie (Tarbiyah STAIN Sorong, 2019)
This study aims to analyze and uncover Ibrahim M. Abu-Rabi's arguments which say that acts of terrorism committed by Muslims are not only related to doctrine, but also related to the historical, social, economic and political roots of the States. Arabic and countries which are predominantly Muslim. This research is literature research by analyzing a book written by Ibrahim M. Abu-Rabi. This research found that the Islamic world is facing complex problems in the social, ethnic and cultural fields. These problems are influenced by the existence of three factors; modernization, nationalization, and religious movements.